Analysis and Optimization of Conditions for the Use of 2',7'-Dichlorofluorescein Diacetate in Cultured Hepatocytes - Megan J. Reiniers; Lianne R. de Haan; Laurens F. Reeskamp; Mans Broekgaarden; Rowan F. van Golen; Michal Heger (MDPI AG, 2021)
Numerous liver pathologies encompass oxidative stress as molecular basis of disease. The use of 2',7'-dichlorodihydrofluorescein-diacetate (DCFH2-DA) as fluorogenic redox probe is problematic in liver cell lines because of membrane transport proteins that interfere with probe kinetics, among other reasons. The properties of DCFH2-DA were analyzed in hepatocytes (HepG2, HepaRG) to characterize methodological issues that could hamper data interpretation and falsely skew conclusions. Experiments were focused on probe stability in relevant media, cellular probe uptake/retention/excretion, and basal oxidant formation and metabolism. DCFH2-DA was used under optimized experimental conditions to intravitally visualize and quantify oxidative stress in real-time in HepG2 cells subjected to anoxia/reoxygenation. The most important findings were that: (1) the non-fluorescent DCFH2-DA and the fluorescent DCF are rapidly taken up by hepatocytes, (2) DCF is poorly retained in hepatocytes, and (3) DCFH2 oxidation kinetics are cell type-specific. Furthermore, (4) DCF fluorescence intensity was pH-dependent at pH < 7 and (5) the stability of DCFH2-DA in cell culture medium relied on medium composition. The use of DCFH2-DA to measure oxidative stress in cultured hepatocytes comes with methodological and technical challenges, which were characterized and solved. Optimized in vitro and intravital imaging protocols were formulated to help researchers conduct proper experiments and draw robust conclusions.